Phytoprostanes, phytofurans, tocopherols, tocotrienols, carotenoids and free amino acids and biological potential of sea buckthorn juices. (21st June 2021) - Tkacz, Karolina; Gil‐Izquierdo, Ángel; Medina, Sonia; Turkiewicz, Igor Piotr; Domínguez‐Perles, Raúl; Nowicka, Paulina; Wojdyło, Aneta
Abstract: BACKGROUND: Juices are currently a fast‐growing segment in the fruit and vegetable industry sector. However, there are still no reports on the diversity of the phytochemical profile and health‐promoting properties of commercial sea buckthorn ( Hippophaë rhamnoides ) juices. This study aimed to identify and quantify phytoprostanes, phytofurans by ultra high‐performance liquid chromatography coupled with triple quadrupole mass spectrometry (UHPLC‐QqQ‐MS/MS), tocopherols, tocotrienols by ultra‐performance liquid chromatography coupled with a fluorescence detector (UPLC‐FL), carotenoids, and free amino acids by ultra‐performance liquid chromatography coupled with a photodiode detector‐quadrupole and tandem time‐of‐flight mass spectrometry (UPLC‐PDA‐Q/TOF‐MS), and assess their anti‐cholinergic, anti‐diabetic, anti‐obesity, anti‐inflammatory, and antioxidant potential by in vitro assays of commercial sea buckthorn juices. RESULTS: Phytoprostanes (PhytoPs) and phytofurans (PhytoFs) in sea buckthorn juices were identified for the first time. Juices contained eight F1 ‐, D1 ‐, B1 ‐ and L1 ‐phytoprostanes and one phytofuran (32.31–1523.51 ng and up to 101.47 μg/100 g dry weight (DW)), four tocopherol congeners (22.23–94.08 mg 100 g –1 DW) and three tocotrienols (5.93–25.34 mg 100 g –1 DW). Eighteen carotenoids were identified, including ten xanthophylls, seven carotenes and phytofluene, at a concentration of 133.65 to 839.89 mg 100 g –1 DW. Among the 20 amino acids (175.92–1822.60 mg 100 g –1 DW), asparagine was dominant, and essential and conditionally essential amino acids constituted 11 to 41% of the total. The anti‐enzyme and antioxidant potential of juices correlated selectively with the composition. CONCLUSION: Sea buckthorn juice can be a valuable dietary source of vitamins E and A, oxylipins and amino acids, used in the prevention of metabolic syndrome, inflammation, and neurodegenerative processes. The differentiation of the composition and the bioactive potential of commercial juices indicate that, for the consumer, it should be important to choose juices from the declared berry cultivars and crops. © 2021 Society of Chemical Industry.